2023
DOI: 10.1108/ijppm-01-2022-0055
|View full text |Cite
|
Sign up to set email alerts
|

Board diversity on firm performance from resource-based view perspective: new evidence from Pakistan

Abstract: PurposeThis study aims to investigate the impact of extensive board diversity on firm performance from the perspective of resource-based view (RBV) theory in the context of Pakistan.Design/methodology/approachThe analyses are made using a panel random-effects model and generalized method of moment (GMM) across 188 non-financial firms listed in the Pakistan Stock Exchange (PSX) over the period of 2009–2020. The robustness of findings is checked through alternative measurements of the variables and alternative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 120 publications
(234 reference statements)
1
17
0
Order By: Relevance
“…The findings support the resource-based view that foreign directors provide the company with access to a broader social network, diverse and international expertise and communication skills (Beji et al , 2021) and bring new ideas and perspectives into the business (Hafsi and Turgut, 2013), all of which improve financial performance and save the firm from FD. Furthermore, the findings corroborate the idea that boards with international directors may have superior financial performance as a result of their worldwide experience (Sarhan et al , 2019; Ararat et al , 2015; Estelyi and Nisar, 2016; Khan et al , 2023).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The findings support the resource-based view that foreign directors provide the company with access to a broader social network, diverse and international expertise and communication skills (Beji et al , 2021) and bring new ideas and perspectives into the business (Hafsi and Turgut, 2013), all of which improve financial performance and save the firm from FD. Furthermore, the findings corroborate the idea that boards with international directors may have superior financial performance as a result of their worldwide experience (Sarhan et al , 2019; Ararat et al , 2015; Estelyi and Nisar, 2016; Khan et al , 2023).…”
Section: Resultssupporting
confidence: 78%
“…Furthermore, in line with the resource-based view, these internal resources should be prioritized because it will reduce the firm’s FD through the emphasis on CSR. Second, policymakers and regulators should encourage PSX-listed enterprises to appoint board members with suitable educational resources to improve firm performance and keep it out of FD, as irrelevant educational background reduces firm performance (Khan et al , 2023). It is further suggested that PSX-listed companies link the board of directors’ tenure to the company’s performance in terms of profitability, investment effectiveness and CSR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corporate leaders emphasize board members with diverse backgrounds, such as heterogeneity in experience, skills and knowledge (Gabaldon et al, 2018;Guizani and Abdalkrim, 2022). The resource dependency view suggests that board diversity could lead to MD 61,6 a complete appraisal of strategic matters and improve the board's decision quality and creativity (Harrison and Klein, 2007;Khan et al, 2023a;Milliken and Martins, 1996) Therefore, the study hypothesizes as follows:…”
Section: Cognitive Board Diversity and Financial Distressmentioning
confidence: 99%